Comparison of professional values between nursing students in Taiwan and China - Lin, Yu-Hua (Nursing ethics, 2016)
Background:People in both Taiwan and China originally descended from the Han Chinese, but the societies have been separated for approximately 38 years. Due to different political systems, variations exist in healthcare and nursing education systems in Taiwan and China.Objective:The purpose of this study was to examine the professional values of nursing students in Taiwan and China.Design:A cross-sectional design was applied in this study. The Nursing Professional Value Scale–Revised was used to measure the professional values of the students. The questionnaire was distributed to eligible undergraduate students in a classroom setting.Ethical considerations:This study was approved by the Institutional Review Board at the first investigator’s university. Participants were informed that completion and return of the questionnaire was voluntary, and confidentiality was ensured by keeping the responses anonymous.Participants:A convenience sample included 292 Taiwanese students and 654 Chinese students.Findings:A total of 11 individual Nursing Professional Value Scale–Revised items showed significant differences between the two groups. These results reflect the differences in the perceived importance of these items between the groups. There was no significant difference between the two groups in the mean overall scores for the Nursing Professional Value Scale–Revised (p = .766) and three subscales (all p > .05).Conclusion:There are some differences in professional values between nursing students in Taiwan and China. Given the increasingly frequent and close interactions between Taiwan and China and the globalization of nursing, understanding these differences may help nursing educators identify students’ perceptions of their professional values and support the development of strategies to improve weaknesses in professional values.